MELATONIN – WORKING IN COLLABERATION WITH THE CCG TO REDUCE COSTS. Issue 9 (17th August 2016) - Haley, Helen
Abstract : Aim: To reduce the overall expenditure on melatonin for the local health economy by working collaboratively with the CCG's. To ensure that all paediatric patients prescribed melatonin have been clinically assessed by a specialist and the most appropriate formulation is dispensed. Method: Evaluation of GP melatonin prescribing cost across CCG using ePACT data and extrapolation of equivalent cost of prescribing and dispensing within secondary care. This initial data was then refined to exclude patients 16 years and over on unlicensed formulations of melatonin and all patients on licensed formulations. This was used to estimate the net potential saving achieved by repatriating the prescribing of melatonin for children for the local CCG's. A six month pilot was initiated to establish if the predicted savings translated into reality for the local health economy. Results: It was estimated that approximately 100 patients under 16 years were prescribed melatonin by GP's in the local CCG's, 60 of these patients were on unlicensed formulations hence eligible for the pilot. To date we have received 42 referrals from GP's to review the prescribing of melatonin unlicensed formulations. 32 patients had been initiated melatonin by the child development team or paediatric specialist 16 (50%) of whom were currently under the care of the team and being reviewed every six months. 10 of the referrals were for patients under the care of CAMHs who were happy to provide ongoing treatment to avoid duplicated appointments. From the remainder of the referrals 6 patients when contacted had advised that they were no longer using melatonin. The remaining 10 patients have an appointment to review treatment and if deemed appropriate provide ongoing prescriptions using formulations approved by pharmacy. There are still 18 patients prescribed melatonin by Gp's who have not been referred and the medicines management team are chasing. A review of ePACT data for the CCG at the end of the six month pilot compared with the recharge expenditure demonstrated that the predicted net cost of the repatriation was cost neutral for the CCG whilst delivering a predicted saving for the hospital of around £30, 000 per annum. Additional savings for the CCG are anticipated once the remainder of the patients are repatriated. Conclusions: The initial assumption that all unlicensed melatonin prescribing within the local CCG's was for children with severe learning difficulties was unfounded with a number of GP's prescribing these formulations for adults. Consequently the initial projected savings were an overestimate as only paediatric patients would be repatriated as part of this proposal. The hospital expenditure on melatonin had also increased from the original projections due to increasing patient numbers with GP's unwilling to take on the ongoing prescribing. In addition the child development team had started to use Circadin off label for older patients ensuring cost containment for GP's when patients discharged from the child health team. Despite these barriers to success the overall impact of the repatriation process was cost neutral for the CCG.